MENTAL HEALTH AND STRESS MANAGEMENT ISSUES OF POLICE PERSONNEL (BOTH PROFESSIONAL AND DOMESTIC FRONT): A CASE STUDY OF AZAMGARH DISTRICT, UTTAR PRADESH - Dr Payal, Dr. Nisha Tewatia, Dr Deepak Kumar (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2014)
A police force is a constituted body of persons empowered by the state to enforce the law, protect property and limit civil disorder. Their powers include the legitimized use of force. The term is most commonly associated with police services of a sovereign state that are authorized to exercise the police power of that state within a defined legal or territorial area of responsibility. Police forces are often defined as being separate from military or other organizations involved in the defense of the state against foreign aggressors, however, gendarmerie are military units charged with civil policing. Law enforcement, however, constitutes only part of policing activity. Policing has included an array of activities in different situations, but the predominant ones are concerned with the preservation of order. In some societies, in the late 18th and early 19th centuries, these developed within the context of maintaining the class system and the protection of private property. Many police forces suffer from police corruption to a greater or lesser degree. The police force is usually a public sector service, meaning they are paid through taxes. Alternative names for police force include constabulary, gendarmerie, police department, police service, crime prevention, protective services, law enforcement agency, civil guard or civic guard. At present the police departments are facing not only crime problems but also physical and mental problems. Stress, social and economic problems are the challenge for the police department. The police officers and other employees face numerous such kinds of problems. The present research study is an attempt to identify the life changing issues faced by the police personnel and their family. The study also talks about the social re-adjustment and level of stress and other issues related to mental health faced by the police personnel at the professional and domestic front. Keywords: Police personnel, social re-adjustment, mental health, stress management.